Posture defects and the speed of the centre of foot pressure in children of school age - Wilczyński, Jacek; Lipińska-Stańczak, Magdalena; Szaraniec, Katarzyna (Medical Studies/Studia Medyczne, 2014)
Introduction : The development of civilisation and the modern lifestyle of children and teenagers have caused an increase in the number of cases of faulty body posture. Aim of the research: To analyse the relationship between posture defects and the speed of the centre of foot pressure in school-age children. Material and methods: The research included 503 girls and boys aged 12–15 years. The research approach used a spatial photogrammetry technique. Lateral speed and anteroposterior speed of the centre of foot pressure were tested on a Cosmogamma platform. Results : Lateral speed ranged from 8.22 mm/s with eyes open to 7.63 mm/s with eyes closed. In correct posture, from 8.45 mm/s with eyes open to 7.64 mm/s with eyes closed. In the defective posture, from 7.90 mm/s with eyes open to 7.63 mm/s with eyes closed. Antero-posterior speed varied from 10.50 mm/s with eyes open to 10.56 mm/s with eyes closed. In the correct posture, from 10.73 mm/s with eyes open to 10.64 mm/s with eyes closed. In the defective posture, from 10.17 mm/s with eyes open to 10.45 mm/s with eyes closed. Conclusions: Analysis of variance of lateral speed showed a significant effect only of test options (p < 0.002). Lateral speed in the test with eyes closed significantly decreased both in the correct and defective posture. There were no significant differences, however, in lateral speed between the correct and incorrect posture. Analysis of variance did not show any significant effects for anteroposterior speed.